2020
DOI: 10.1186/s40623-020-01268-1
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of near-field tsunami forecasting method using ocean-bottom pressure sensor network (S-net)

Abstract: Since the installation of a dense cabled observation network around the Japan Trench (S-net) by the Japanese government that includes 150 sensors, several tsunami forecasting methods that use the data collected from the ocean floor sensors were developed. One of such methods is the tsunami forecasting method which assimilates the data without any information of earthquakes. The tsunami forecasting method based on the assimilation of the ocean-bottom pressure data near the source area was developed by Tanioka i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Recent studies have started to utilize S-net ocean-bottom seismometers to investigate the seismotectonics and geodynamics in the Tohoku subduction zone (Dhakal et al, 2021;Hua et al, 2020;Matsubara et al, 2019;Nishikawa et al, 2019;Sawazaki & Nakamura, 2020;Takagi et al, 2019Takagi et al, , 2020Tanaka et al, 2019;Uchida et al, 2020;Yu & Zhao, 2020). The S-net also incorporates ocean-bottom pressure gauges (OBPGs), which are expected to be utilized for tsunami forecasts (e.g., Aoi et al, 2019;Inoue et al, 2019;Mulia & Satake, 2021;Tanioka, 2020;Tsushima & Yamamoto, 2020;Wang & Satake, 2021;. The other potential contributions to the earth sciences of the S-net OBPG have also been demonstrated, such as understanding the wave propagation process in the ocean as well as the rupture process of subseafloor earthquakes Kubota et al, 2021;Saito et al, 2021).…”
mentioning
confidence: 99%
“…Recent studies have started to utilize S-net ocean-bottom seismometers to investigate the seismotectonics and geodynamics in the Tohoku subduction zone (Dhakal et al, 2021;Hua et al, 2020;Matsubara et al, 2019;Nishikawa et al, 2019;Sawazaki & Nakamura, 2020;Takagi et al, 2019Takagi et al, , 2020Tanaka et al, 2019;Uchida et al, 2020;Yu & Zhao, 2020). The S-net also incorporates ocean-bottom pressure gauges (OBPGs), which are expected to be utilized for tsunami forecasts (e.g., Aoi et al, 2019;Inoue et al, 2019;Mulia & Satake, 2021;Tanioka, 2020;Tsushima & Yamamoto, 2020;Wang & Satake, 2021;. The other potential contributions to the earth sciences of the S-net OBPG have also been demonstrated, such as understanding the wave propagation process in the ocean as well as the rupture process of subseafloor earthquakes Kubota et al, 2021;Saito et al, 2021).…”
mentioning
confidence: 99%
“…Understanding the mechanisms of seafloor pressure variations is important for multiple scientific disciplines. Besides its wide use in studying various types of ocean dynamics such as interannual upwelling variations, seasonal circulation variations, mesoscale oceanic eddies, ocean currents (e.g., Chelton et al, 2007;Hughes et al, 2018;Osborne & Burch, 1980;Saldías et al, 2021;Thomson et al, 2014), and tsunami generation and propagation (e.g., Kubota et al, 2022;Mulia & Satake, 2021;Tanioka, 2020;Thomson et al, 2011), seafloor pressure monitoring has been used as a geodetic tool to monitor crustal deformation associated with submarine earthquakes and slow slip events (Davis et al, 2015;Hino et al, 2014;Ito et al, 2013;Sun et al, 2017;Wallace et al, 2016). For the same purpose, many recent studies were focused on untangling the mixed oceanographic and geophysical signals in ocean bottom pressure records (Dobashi & Inazu, 2021;Fredrickson et al, 2019;Gomberg et al, 2019;He et al, 2020;T.…”
Section: Introductionmentioning
confidence: 99%
“…larger-scale forearc structure and geodynamic processes (Hua et al, 2020;Uchida et al, 2020;Yu & Zhao, 2020), and enabling real-time earthquake monitoring and tsunami early warning (Aoi et al, 2019;M. Inoue et al, 2019;Mulia & Satake, 2021;Tanioka, 2020;Thomson et al, 2011). To date, studies of offshore earthquake monitoring in real time via cable-connected networks were mostly focused on small earthquakes (up to M w 7.1) (e.g., Kubota, Kubo, et al, 2021;Tréhu et al, 2018;Wallace et al, 2016).…”
mentioning
confidence: 99%
“…Furthermore, it has been reported that much smaller tsunamis with amplitudes less than one centimeter related to the Mw 6.0 Off‐Iwate earthquake on August 20, 2016, were observed (Kubota, Saito, & Suzuki, 2020; Figure 1c). S‐net is also expected to be utilized for the real‐time tsunami forecasts (e.g., Inoue et al., 2019; Suzuki et al., 2020; Tanioka, 2020; Tsushima & Yamamoto, 2020). In addition to earthquake‐induced tsunamis, or seismic tsunamis, the OBPs can record other oceanographic phenomena, such as infragravity waves and internal tides (e.g., Fukao et al., 2019; Tonegawa et al., 2018).…”
Section: Introductionmentioning
confidence: 99%